The Development of eLisa Business Process Models in Achieving University Learning Objectives - Gunadi - Emmanuel (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Factors of the rapid development of information technology, diversity of user needs, and the achievement of university learning goals are general considerations in the management and development of online learning methods (eLearning). In general, university leaders appoint certain units for the management and development of eLearning. In carrying out its functions, eLearning developer units often experience limitations and stagnation in dealing with the three factors above. How the development of university eLearning has the support of all university components and is in line with the goals and business processes of university learning is a challenge for the sustainability of university eLearning. This study collaborates the instructional process of Education Enterprise Architecture business architecture with the learning objectives of Universitas Gadjah Mada. By analyzing the business processes of eLisa Universitas Gadjah Mada and developing the concept of eLisa business processes, the study produced changes in the concept of eLisa business processes. The use of EEA instructional process items by 77.4% in eLisa business processes resulted in changes in the learning process scenarios with eLisa. These changes encourage more concrete involvement of internal units at UGM in developing the learning process at eLisa. The direction of the learning process at eLisa which is oriented towards meeting the learning needs of students independently and interdisciplinary is in line with the goals of the university learning process.